Development of a Two-Stage Middlings Circuit at Inco’s Clarabelle Mill Part 1: Laboratory Studies - Manqiu Xu; Pete Quinn; Glen Robertson; Steve Wilson (Canadian Institute of Mining, Metallurgy and Petroleum, 2000)
"The middlings circuit, once called the pyrrhotite rejection circuit, at Inco’s Clarabelle mill was a single flotation stage. It used to process a combined feed consisting of the main flotation scavenger concentrate and the non-magnetic portion of the magnetics flotation circuit tails. The typical circuit metallurgy was 55% nickel recovery at 6.5% Cu+Ni concentrate grade. In the past few years, a research project with the objective of improving the circuit metallurgy was initiated between Inco’s research laboratory and the Mill’s Process Technology group. This project has gone through three steps: a) initial laboratory studies, b) on-site pilot plant investigation, and finally c) full plant implementation.The present paper describes the initial laboratory test work. The development of a two-stage circuit consisting of separate rock and pyrrhotite rejection stages to replace the simultaneous rejection of both rock and pyrrhotite in a single stage is discussed. A two-stage circuit simulation based on batch laboratory flotation data is also presented. Further development work, including the on-site pilot plant test work and the plant implementation of the new circuit design, will be described in a later publication.INTRODUCTIONThe milling operation at Inco’s Clarabelle mill, Copper Cliff, Ontario processes a rich complex sulfide ore from several large production mines around the Sudbury basin (Agar, 199 1). The sulfide mineralization is simple, consisting of chalcopyrite (Cp), pentlandite (Pn) and pyrrhotite (Po). The main gangue minerals are pyroxene, feldspar and quartz with minor amphibole and talc. Estimates of mineral composition are routinely calculated from Cu, Ni and S assays. In the mineralogical calculations, all gangue minerals are conveniently grouped and treated as rock (Rk)."